Adhesive and Abrasive Wear Properties of Nanoclay-Modified Chopped Kenaf Fiber Reinforced Polymer Composites - Jumahat, Aidah; Adilah Abu Talib, Anis; Faizuddin Tg Mohd Azmi, Tg; Adzummar Hakim Abdull Adziz, M (International Journal of Engineering and Technology, 2018)
The present work investigates the effect of nanoclay incorporation on wear properties of kenaf fiber reinforced polymer (KFRP) composites. The nanoclay/epoxy composites with 1.0wt%, 3.0wt% and 5.0wt% nanoclay contents were mixed using mechanical stirrer and high shear three roll mill machine, while chopped KFRP composites were fabricated using high vacuum and hand lay-up methods.The composites were tested under adhesive and abrasive wear conditions, where the specimens slide against smooth pin and vitrified bonded silicon carbide wheel, respectively. The operating parameters were fixed at 30N load, 300rpm speed and 10km distance in order to evaluate the effect of nanoclay on adhesive and abrasive wear properties of chopped kenaffibre reinforced epoxy polymer composites. The presence of kenaf fiber has significantly improved the wear properties of epoxy resin in both test conditions. Nanoclay incorporation has improved wear properties of KFRP composite up to 50.9% under adhesive wear and 59.2% under abrasive wear. Therefore, reinforcing kenaf fiber and nanoclay together can give synergistic impact and potentially improve the adhesive and abrasive wear properties of epoxy polymer.Â Â